Management of Acute Respiratory Distress Syndrome (ARDS): A Review of Current Ventilatory and Pharmacological Strategies - Pielacinski, Jan; Szymon Pucyło; Nieczyporuk , Mateusz; Skweres, Martyna; Piotrowska, Gabriela; Ceglarz, Katarzyna; Rudnik, Aleksander; Sikora, Kinga (Journal of Education, Health and Sport, 2025)
Introduction and Purpose. Acute Respiratory Distress Syndrome (ARDS) is a severe inflammatory lung condition associated with high mortality. Despite advances in intensive care, optimal management remains a challenge. This review synthesizes current ventilatory and pharmacological strategies, emphasizing precision medicine to improve outcomes. Material and Methods. A comprehensive literature search was conducted using PubMed and Google Scholar, focusing on ARDS management studies published since 2015. Keywords included "ARDS," "mechanical ventilation," "prone positioning," "pharmacological therapy," and "precision medicine." Brief Description of the State of Knowledge. Lung-protective ventilation, utilizing low tidal volumes and prone positioning, significantly reduces mortality in ARDS. Positive end-expiratory pressure (PEEP) optimization and extracorporeal membrane oxygenation (ECMO) serve as adjunct strategies in severe cases. Pharmacological approaches, including early corticosteroid administration and neuromuscular blocking agents, show selective benefits, particularly in hyperinflammatory ARDS phenotypes. Novel therapies, such as mesenchymal stem cells, IL-1β inhibitors, and machine learning-assisted ventilation strategies, represent promising future directions. Conclusions. ARDS management is evolving toward a personalized, phenotype-driven approach integrating ventilatory and pharmacological strategies. Despite significant advances, challenges remain in optimizing corticosteroid use, PEEP titration, and ECMO application. Future research should focus on biomarker-driven therapies and artificial intelligence-assisted ventilation to enhance patient outcomes and reduce mortality.